Pengujian Katalis ZnO Presipitan Zink Karbonat Pada Transesterifikasi CPO FFA Tinggi - Desadria, Renny; Yusnimar, Yusnimar; Helianty, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Crude palm oil (CPO) with a free fatty acid content (ALB) high crude can be processed into biodiesel. At present, various types of catalysts have been investigated for the process of making biodiesel from vegetable oils that have high levels of ALB, which of one is ZnO. This study aims to synthesis ZnO catalyst of precipitant ZnCO3 and is used as a catalyst in the process tranesterifikasi crude oil into biodiesel. The catalyst that has recycle synthesized and analyzed by FTIR, and the results compared with the FTIR spectrum of ZnO (Merck). Based on the results of FTIR analysis, synthesis catalyst ZnO fresh and ZnO catalyst which has been recycle the spectrum as the spectrum of ZnO p.a (Merck). After ZnO catalyst used, the catalyst in the recycle and reuse of the reaction to determine reusability ZnO catalyst in crude yield of biodiesel produced. Based on the results of the study, 90.78% yield crude biodiesel obtained from the reaction using fresh ZnO catalyst, crude biodiesel yield 85.46% for the reaction using ZnO catalyst which has been in the recycle first, crude biodiesel yield 75.67% and 70.98 % for reactions using ZnO catalyst which has been in the recycle second and third times. Biodiesel produced has a density of 870.51 to 887.58 kg / m3, kinematic viscosity of 5.76 to 5.77 mm2 / s, the flash point of 143-170 Â° C, acid number 0.76 -0.79 mg-KOH / g -biodiesel and alkyl ester content of 96.54 to 96.67%. Keywords : crude biodiesel, characterization of ZnO, crude palm oil (CPO), FTIR spectrum, recycle, transesterification.